Lifestyle Factors and Perceptions of Diabetes Among Individuals in North India - Eric Kwasi Elliason; Atul Khajuria; Stepehn Monday; J.Samuel Kamanda; Christian Gendemeh (International Journal of Tropical Medicines, 2025)
Background: Diabetes mellitus is influenced by a complex interplay of genetic, environmental, and lifestyle factors. In North India, unique socio-cultural and dietary patterns shape individual behaviors and perceptions toward diabetes. Understanding these lifestyle choices and cultural beliefs is critical for designing interventions that improve adherence to medical treatment and promote healthier outcomes. Methods: A cross-sectional survey was conducted among 1,500 individuals diagnosed with diabetes across selected urban and rural districts in North India. A structured and validated questionnaire assessed dietary habits, physical activity, use of alternative medicine, medication adherence, and perceptions about diabetes. Data were collected through face-to-face interviews and an online survey. Descriptive statistics, chi-square tests, and significance testing (p Results: The majority of participants (59.3%) reported high-carbohydrate intake, and only 48% engaged in regular physical activity (≥3 times per week). While 68.3% adhered regularly to prescribed medication, only 27.3% practiced consistent blood glucose monitoring. Alternative medicine was used by 41% of respondents. Most participants (73.7%) perceived diabetes as manageable, and 64.7% reported that family influenced their dietary decisions. Belief in traditional remedies was more common among rural and older individuals. Poor lifestyle adherence was significantly associated with rural residence, lower education, and lower socio-economic status (p Conclusion: Diabetes self-management in North India is challenged by high-carbohydrate diets, irregular physical activity, and widespread belief in alternative remedies. Cultural perceptions, family influence, and socio-demographic factors significantly shape health behaviors. Targeted education, culturally sensitive interventions, and community engagement are essential to improve lifestyle practices and perceptions of diabetes management in this region.
Keywords: Alternative medicine; Diabetes mellitus; cultural perception; dietary habits; lifestyle behaviors; north India; physical activity; self-management